2016
DOI: 10.12659/msm.899571
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glycemic Control in Insulin-Dependent Diabetics with Depression by Concomitant Treatment with Antidepressants

Abstract: BackgroundIt is still disputable whether negative effects of comorbid depression in diabetics can be diminished by successful treatment of depression. The primary aim of this study was to assess whether addition of antidepressants to existing insulin treatment would further improve glycemic control in these patients. A secondary objective was to assess whether such treatment impairs their lipid and inflammatory status.Material/MethodsTotal of 192 patients with poorly controlled diabetes (defined as HbA1c ≥8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
1
6
2
3
Order By: Relevance
“…En la muestra estudiada predominó la ausencia de trastorno tanto para ansiedad como para depresión. Sin embargo, diversos estudios han indicado una mayor prevalencia de síntomas de depresión y ansiedad en pacientes con DM tipo 2, evidenciando una relación de dichos trastornos con el control glucémico (23,24). Por su parte, Pokrajac, Kukić, Klobučar y Tkalčić en un estudio similar reportaron que el 76,3% de los pacientes no estaban ansiosos y el 73,8% de los pacientes no presentaban síntomas de depresión (25).…”
Section: Discussionunclassified
“…En la muestra estudiada predominó la ausencia de trastorno tanto para ansiedad como para depresión. Sin embargo, diversos estudios han indicado una mayor prevalencia de síntomas de depresión y ansiedad en pacientes con DM tipo 2, evidenciando una relación de dichos trastornos con el control glucémico (23,24). Por su parte, Pokrajac, Kukić, Klobučar y Tkalčić en un estudio similar reportaron que el 76,3% de los pacientes no estaban ansiosos y el 73,8% de los pacientes no presentaban síntomas de depresión (25).…”
Section: Discussionunclassified
“…One possible explanation might be indication bias; that is, without the sexual dysfunction complication, the dosage of serotonergic agents such as SSRIs may be increased or they may be replaced with another antidepressant agent. Another study indicated that when depressive symptoms improved in patients who had DM with comorbid depression, glycemic control also improved 24 Cross-sectional studies have also reported associations between improved glycemic control and ameliorated sexual dysfunction in men with DM. 25,26 DM itself may affect sexual function through multiple pathophysiological pathways and have vascular, neurological, and hormonal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Спроби покращити контроль глікемії шляхом використання в комплексній терапії синтетичних антидепресантів дали неоднозначні результати: як позитивні для окремих препаратів [8,9], так і відсутність впливу на вуглеводний обмін [10]. Існують дані, що за ефективністю дії у хворих з легкою та помірною депресією рослинні препарати, що містять звіробій, компонент, що забезпечує доведений антидепресивний ефект, не поступаються синтетичним антидепресантам [11], але мають кращу, ніж у синтетичних сполук, переносимість [12].…”
Section: вступunclassified